The EFFECTIVENESS OF BRUNO MARS SONG IN DOO-WOPS & HOOLIGANS ALBUM ON STUDENTS’ PRONUNCIATION MASTERY at VOCATIONAL HIGH SCHOOL KARTIKATAMA METRO - Faliyanti, Eva; Siagiyanto, Bambang Eko; Kurniasari, Imas (Universitas Muhammadiyah Metro, 2024)
The aim of this research is to find out the effect and significant difference of bruno mars song in doo-wops & hooligans album for students' pronunciation mastery at Vocational High School Kartikatama Metro. Song is a media in the form of musical works that are suitable for teaching English, especially pronunciation. This research used quasi experimental design. The subjects of this research are the tenth grade students at Vocational High School Kartikatama Metro. The result of data analysis indicates that value of t obtained (to) is lower than value of t table (-16.482<2.074). Moreover, the second data indicates t obtained (to) is lower than value of t table (-13.657<2021). The conclusion are teaching English pronunciation using bruno mars song in doo-wops & hooligans album is effective to increase students' pronunciation mastery and gives a significant differences. Researchers hope that this research can help future researchers to conduct similar research, especially when using English songs to teach pronunciation. Future researchers must use the latest songs in conducting further research.